Beyond paychecks: Demographic insights into job satisfaction among psychologists - Akhi, Antaz Hena; Ahmed, MD. Faisal; Sarkar, Nandita; Akter, Ratna; Binte Siraj, Lamia; Ul-Morshed, Mahadi-; Naz, Hamida; Roy, Shramana Singha (Journal of Indonesian Psychological Science (JIPS), 2025)
Job satisfaction is a fundamental determinant of professionals’ productivity, motivation, and mental well-being. This study explored the level of job satisfaction among psychologists in Bangladesh and examined its association with demographic characteristics. Using a quantitative, cross-sectional, and correlational design, data were gathered from 100 purposively selected psychologists through an online survey. A standardized and culturally adapted job satisfaction questionnaire for Bangla-speaking participants was employed to ensure contextual relevance. Data analysis included descriptive and inferential procedures such as correlation and analysis of variance. The findings revealed a generally moderate level of job satisfaction among participants, with significant variations across educational background, socioeconomic status, residential area, and work experience. Psychologists with higher income or belonging to more privileged socioeconomic groups tended to report lower satisfaction, suggesting that elevated expectations may not always align with workplace realities. These results highlight the complex interplay of contextual and demographic factors shaping professional well-being in Bangladesh’s mental health sector. Although the study’s scope was limited by purposive sampling and its national focus, it provides an important empirical contribution to the limited literature on occupational satisfaction within low-resource contexts. Further research across diverse geographic and institutional settings is recommended to enhance the generalizability of findings. This study contributes to a broader understanding of how demographic and contextual dynamics influence professional satisfaction and can guide the development of culturally sensitive, evidence-based interventions to strengthen the mental health workforce in Bangladesh